2000
DOI: 10.1128/jcm.38.9.3254-3259.2000
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Diagnosis of Scrapie by Immunohistochemistry of Third Eyelid Lymphoid Tissue

Abstract: Ovine scrapie is a member of the transmissible spongiform encephalopathies (TSEs), a heterogeneous family of fatal neurologic disorders characterized by deposition of an abnormal isoform (prion protein [PrP] PrP-Sc) of a cellular sialoglycoprotein in neural tissue. PrP-Sc is detectable in some lymphoid tissues of infected sheep months or years before development of clinical disease. Detection of PrP-Sc in these tissues is the basis for live-animal testing. In this study, we characterize the performance of a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
153
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(158 citation statements)
references
References 29 publications
3
153
1
1
Order By: Relevance
“…This clinical sign has been associated with an alteration in cranial nerves II and VII and the cerebellum, 27 a visual deficit by retinopathy, 49 and a wallerian degeneration of the optic nerve. 50 In conclusion, 3rd eyelid lymphoid tissue biopsies, which are useful for diagnosing preclinical scrapie in sheep, 16,17 are also a crucial tool in sequential clinical studies in naturally scrapie-affected sheep, as demonstrated in this study. Indeed, the diagnosis of affected animals in preclinical stages of the disease allowed the detection of precocious clinical signs, most remarkably hypoesthesia in the limbs.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…This clinical sign has been associated with an alteration in cranial nerves II and VII and the cerebellum, 27 a visual deficit by retinopathy, 49 and a wallerian degeneration of the optic nerve. 50 In conclusion, 3rd eyelid lymphoid tissue biopsies, which are useful for diagnosing preclinical scrapie in sheep, 16,17 are also a crucial tool in sequential clinical studies in naturally scrapie-affected sheep, as demonstrated in this study. Indeed, the diagnosis of affected animals in preclinical stages of the disease allowed the detection of precocious clinical signs, most remarkably hypoesthesia in the limbs.…”
Section: Discussionmentioning
confidence: 71%
“…21 One hundred forty-six sheep were selected on the basis of having genotypes that were susceptible to scrapie (R3 and R4 risk), 22 and these animals constituted an independent flock that was monitored for 18 months under veterinarian supervision and care acording to the National Research Council's guide for animal experimentation. Third eyelid lymphoid tissue biopsies from all 146 animals were taken to test for PrPsc in vivo 16 by immunohistochemical analysis with the L42 antibody a by previously described methods. 20 Results of testing showed that 18 sheep (12.5%) were positive for scrapie and that 128 (87.5%) were negative.…”
Section: Selection Of Animals Prp Genotyping and 3rd Eyelid Biopsiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The one exception was the comparison of the proportion of deer that migrated by sex and CWD status because we were able to define migratory status of VHF-collared deer. We considered all available habitat to present an equal risk of CWD-infection because the area has been endemic for CWD for 50 years (O'Rourke et al 2000), which may allow CWD contamination to become homogenous across an area, particularly riparian habitats. Chronic wasting disease was first detected in deer hunt area 65 in 1999 through both targeted (i.e., suspected clinical CWD cases) and hunter-killed surveillance (W. H. Edwards, personal communication), although surveillance prior to 1999 was minimal.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Thus, it was appropriate to replace Sip terminology with Prnp polymorphisms or PrP genotypes. The ovine Prnp-coding region has been shown to be highly polymorphic, and to date at least 15 apparently mutually exclusive alleles (mono-mutated) have been described, most of which are rare and as yet unrelated to disease development (19,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) (Fig. 2).…”
Section: Polymorphisms In the Coding Region Of Prnp -The Story Of ''Smentioning
confidence: 99%